INDEPENDENSI KEJAKSAAN AGUNG REPUBLIK INDONESIA - Valentino Nathanael Prabowo; Tjondro Tirtamulia; Hesti Armiwulan (CALYPTRA, 2024)
Abstract—This study aims to analyze the independence of the Attorney General's Office in the constitutional system in Indonesia. The research method used in this study is a normative juridical method with a statutory, conceptual, historical, and comparative approach. The results of this study indicate that the Attorney General of the Republic of Indonesia does not have institutional independence in the state administration system in Indonesia. This is because the Prosecutor's Office is a government institution or in other words it is under executive power. In addition, the provisions of Article 19 paragraph (2) of Law Number 16 of 2004 concerning the Attorney General of the Republic of Indonesia also state that the Attorney General is appointed and dismissed by the President. In this case the President has absolute power over the position of Attorney General. If the performance of the Attorney General is contrary to the interests of the President, then the President can dismiss him unilaterally. To address the issue of the independence of the Attorney General's Office, the Attorney General's Office must be positioned as an independent state institution (state auxiliary organ) so that the Attorney General's Office can be free from intervention by any party. Keywords: attorney general's office, independence, power restrictions Abstrak—Penelitian ini bertujuan untuk menganalisis independensi Kejaksaan Agung dalam sistem ketatanegaraan di Indonesia. Metode penelitian yang digunakan dalam penelitian ini adalah metode yuridis normatif dengan pendekatan peraturan perundang- undangan, konseptual, historis, dan komparatif. Hasil penelitian ini menunjukkan bahwa Kejaksaan Agung Republik Indonesia tidak memiliki independensi secara institusional dalam sistem ketatanegaraan di Indonesia. Hal ini dikarenakan Lembaga Kejaksaan merupakan lembaga pemerintahan atau dengan kata lain berada di bawah kekuasaan eksekutif. Selain itu, ketentuan Pasal 19 ayat (2) Undang-Undang Nomor 16 Tahun 2004 tentang Kejaksaan Republik Indonesia juga menyatakan bahwa Jaksa Agung diangkat dan diberhentikan oleh Presiden. Dalam hal ini Presiden memiliki kekuasaan yang absolut terhadap kedudukan Jaksa Agung. Apabila kinerja Jaksa Agung berlawanan dengan kepentingan Presiden, maka Presiden dapat memberhentikannya secara sepihak. Untuk mengatasi persoalan independensi Kejaksaan Agung, maka Kejaksaan Agung haruslah diletakkan sebagai lembaga negara independen (state auxiliary organ) sehingga Kejaksaan Agung dapat terbebas dari intervensi pihak manapun. Kata kunci: Kejaksaan Agung, Independensi, Pembatasan Kekuasaan